Mineral and bone disease in renal transplantation - Ferreira,Ana Carina (2021)
ABSTRACT Chronic kidney disease - mineral and bone disorders (CKD‑MBD) tends to improve or to change phenotypically in the post‑transplant period. Mineral and bone disorders post‑transplantation (MBD‑PT) seem to be associated with high fracture risk and cardiovascular morbidity, and so it is necessary to be aware of its presence to minimize the MBD‑PT impact. In this article we summarize the features of MBD‑PT.